Photocatalytic Inactivation of Bioaerosols: A Short Review on Emerging Technologies - Riaz, Nadia; Khan, Muhammad S.; Bilal, Muhammad; Ullah, Sami; Al-Sehemi, Abdullah G. (Current Analytical Chemistry, 2021)
Background: Formation of the microbial colonies in the wet and damp environment affects the indoor air quality thus posing severe threats to human health. Health problems or Building- associated illness (any disease or infection) caused by being in a closed space or building are generally separated into two categories including building-related illness (BRI) and sick building syndrome (SBS). Considered by Pathognomy research, that biological pollutants or bioaerosols (bacteria, fungi and viruses like coronavirus), are the significant inducement for “sick building syndrome (SBS)” associated with a group of mucosal, skin, and general symptoms, characterized by tiredness; headaches; irritation of skin, nose, eyes, throat and mucous membranes, most prevalent in buildings like residential and occupational like offices, schools, hotels and hospitals. Methods: Currently outdoor air purging, UV light activated air filters, chemical treatment like ozonation and oxidation, are used for the improvement of indoor air quality but these treatment techniques not only produce secondary biological pollutants but are also costly and not effective for a variety of microorganisms. In recent years, nanomaterials in the area of heterogeneous photocatalysis have gained much attention because of their enhanced physicochemical properties including particle size, surface area, dopant dispersion and interaction with the support (Titanium). Results: Heterogeneous photocatalysis systems have been reported to produce self-cleaning materials and to solve a range of environmental problems like air and water detoxification. Among various heterogeneous photocatalysts, TiO2 gained much attention due to its non-toxic nature, high stability, excellent photocatalytic ability, self-cleaning and antibacterial properties and most of all low cost and commercial availability. It is among the basic materials being used in various commercial products like as white pigment in paints for building coating. The antibacterial properties are associated with the generation of reactive oxygen species (ROS) in the presence of a light source. Conclusion: Some of the reported TiO2 nanomaterials-based air-filters and building coatings are reported with the major drawbacks like lower surface area, inactivation in the absence of light (dark) and activation only under UV light irradiation. Thus, the requirement for cost effective, safer and energy efficient materials is the need of the day.
Keywords: Antibacterial activities